The multiple functions of the numerous Chlamydia trachomatis secreted proteins: the tip of the iceberg - Joana N. Bugalhão; Luís Jaime Mota (Microbial Cell, 2019)
Chlamydia trachomatis serovars are obligate intracellular bacterial pathogens mainly causing ocular and urogenital infections that affect millions of people worldwide and which can lead to blindness or sterility. They reside and multiply intracellularly within a membrane-bound vacuolar compartment, known as inclusion, and are characterized by a developmental cycle involving two morphologically and physiologically distinct chlamydial forms. Completion of the developmental cycle involves the secretion of > 70 C. trachomatis proteins that function in the host cell cytoplasm and nucleus, in the inclusion membrane and lumen, and in the extracellular milieu. These proteins can, for example, interfere with the host cell cytoskeleton, vesicular and non-vesicular transport, metabolism, and immune signalling. Generally, this promotes C. trachomatis invasion into, and escape from, host cells, the acquisition of nutrients by the chlamydiae, and evasion of cell-autonomous, humoral and cellular innate immunity. Here, we present an in-depth review on the current knowledge and outstanding questions about these C. trachomatis secreted proteins.